2020
DOI: 10.3390/agronomy10111727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Treatments and Amendments on the Nematode Community under Miscanthus Growing in a Lead Contaminated Military Site

Abstract: Applying phytotechnologies with energy crops on lands contaminated with trace elements provides cellulosic biomass and improves soil health. The process can be reflected in changes in the soil nematode community structure. This study assessed the nematode community composition of soil with Miscanthus grown with different agronomic practices. The research was conducted at Fort Riley, Kansas, USA, in soil with aged contamination by Pb at 1000 to 1500 mg/kg. The experimental design was a randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 77 publications
0
22
0
1
Order By: Relevance
“…According to 'Shelford's law of tolerance', all populations staying in the optimal condition do not demonstrate an unambiguous response to the ecological factors (Shelford, 1931). In contrast, switching the ecological factor from the pessimum to the optimum is commonly accompanied by the sensitive reaction of populations (Alasmary et al, 2020;Kunah et al, 2018). It is possible to assume that the species which are in an optimum zone do not appear insensitive to the variability of environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to 'Shelford's law of tolerance', all populations staying in the optimal condition do not demonstrate an unambiguous response to the ecological factors (Shelford, 1931). In contrast, switching the ecological factor from the pessimum to the optimum is commonly accompanied by the sensitive reaction of populations (Alasmary et al, 2020;Kunah et al, 2018). It is possible to assume that the species which are in an optimum zone do not appear insensitive to the variability of environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The main function is to contain the contaminated material. However, this is usually combined with adding soil amendment to reduce contaminant movement in soil (e.g., phytostabilzation of Pb contaminated military site soil using Miscanthus in combination with P amendments (Alasmary et al, 2020)). This process is used to limit the movement of contaminants with water.…”
Section: Phytohydraulicsmentioning
confidence: 99%
“…Results from 2016 to 2018 showed that one-time addition of soil amendments to Pb-contaminated soil supports establishing and stabilizing Miscanthus, increasing biomass yield as well as reducing phytoavailability and bioaccessibility of Pb (as measured by physiological-based extraction test procedure developed by Ruby et al (1996) and modified by Medlin (1997)). Moreover, biosolids-treated plots showed improved soil enzyme activities, organic carbon, and microbial biomass (Alasmary et al, 2020). X-ray absorption spectroscopy results indicated pyro morphite, Pb associated with Fe minerals, and Pb adsorbed to humic acid were the dominant Pb species in P-amended and nonamended soils (Unpublished data, Alasmary and Hettiarachchi).…”
Section: Figure 29mentioning
confidence: 99%
“…Технологічне вдосконалення фітотехнологій ґрунтується на застосуванні різних агротехнічних, агрохімічних та біотехнологічних заходів (Verma et al, 2016;Alasmary et al, 2020;). При вирощуванні міскантусу на чорноземі типовому найвищі показники біопродуктивності рослин були отримані за комбінованої обробки рістстимулювальними біопрепаратами Квантум Голд та Вимпел-К: після проведення дворазової позакореневої обробки та обприскуванням під час вегетації (Katelevsky, 2020).…”
Section: обговоренняunclassified